Immunomodulatory and Antioxidant Effects of Lactiplantibacillus plantarum PQ104969 on Gastrointestinal Damages following Subacute Administration of Indomethacin in Wistar Rats - Oladejo, Babayemi Olawale; Omayone, Tosan Peter; Bamigbade, Bukky Onyemowo; Timothy, John Oluwaseyi; Oseyemi, Oluwaseun; Oshaniwa, Christianah Omowunmi; Oyebola, Ayomiposi Emmanuel (Bangladesh Journal of Microbiology, 2025)
The accumulation of immune effector cells often exacerbates inflammatory response. This study assessed the therapeutic effects of Lactiplantibacillus plantarum PQ104969 on gastrointestinal inflammation induced by subacute administration of indomethacin in Wistar albino rats with emphasis of the effect on the stomach, ileum and colon. Twenty-four (24) male Wistar rats were divided into four groups: control group A received normal saline; group B were induced with indomethacin (7 mg/kg); group C were treated with 5 x 107 CFU/ml L. plantarum PQ104969, while positive control group D were treated with Omeprazole (20 mg/kg). The stomach, ileum and colon of all groups were harvested after 7 days treatment and analyzed for their organ weight, malondialdehyde (MDA) concentration, glutathione (GSH) level, total antioxidant capacity (TAC) and protein concentration. Serum level of interleukin 10 (IL10) and immunoglobulin g (IgG) were determined using ELISA technique. Tissue histology of the selected organs was done using routine haematoxylin and eosin staining technique. L. plantarum PQ104969-treated group had significantly higher glutathione levels and reduced MDA levels in the colon compared to the indomethacin group. The total antioxidant capacity (TAC) was elevated in this group, though lower than in the positive control. Both L. plantarum and omeprazole groups experienced a reduction in relative colon weight, while protein concentrations in gastrointestinal organs were consistent across groups. An increase in IL10 and IgG levels, along with milder epithelial erosion, indicated reduced inflammation. The study demonstrates that L. plantarum PQ104969 mitigates indomethacin-induced gastrointestinal damage in Wistar rats through antioxidant and immunomodulatory mechanisms, which offer a promising therapeutic approach for gastrointestinal damages. Bangla. J. Microbiol. 2025, Vol. 41, P: 1-10